Optimizing local wisdom in coffee entrepreneurship to strengthen cultural identity in Pangalengan - Muhamad Ikhsan Qurota’ayun; Grisna Anggadwita (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2026)
In the era of globalization, local entrepreneurs face increasing challenges in preserving cultural identity while maintaining business sustainability. This study examines how local wisdom is integrated into coffee entrepreneurship in Pangalengan, West Java. Using a qualitative case study method, data were collected through interviews with six local entrepreneurs and analyzed using the Gioia approach. The findings show that local values are reflected in farming, processing, marketing, and community collaboration. Two key dimensions emerged: preservation of local coffee culture and innovation in sustainable entrepreneurship. This study enriches cultural entrepreneurship literature and offers insights for MSME development in culturally rooted rural areas.